Obstacles to Applying the Re-Engineering in Public Secondary Schools in the Suburbs of Jerusalem - Alkhatib, Aatka AbdRabo; Abu Khairan, Ashraf Mohammed (Journal of Educational and Psychological Sciences, 2024)
This study aimed to reveal the obstacles to Applying the re-engineering in public secondary schools in the suburbs of Jerusalem, to achieve these objectives, the analytical descriptive approach was used a questionnaire tool, as they were applied to a stratified survey sample of (73) principals, two deputy principals, and administrative assistants working in schools in the suburbs of Jerusalem. After conducting the statistical analysis, the results shwo that: 1.There are obstacles when applying reengineering, and they were, respectively, physical obstacles with a high degree, then administrative obstacles with a high degree as well, amounting, then human obstacles with a moderate degree, then obstacles Technique with an average score. 2.There were no statistically significant differences in the averages of the opinions of the study sample about the obstacles to applying reengineering in government secondary schools due to the variables of gender and years of experience, while it was clear that there were differences due to the academic degree variable in favor of a master’s degree or more, and there were differences due to the number of courses variable. The study recommended, most notably the development of the work of the school administration in line with proper planning to transfer the concept of engineering to school principals and administrators, in order to develop the ability to apply modern administrative concepts, and to increase the financial allocations for technological means to support the application of engineering, and paying attention to the budgets allocated for research and studies in the field of engineering.